Impacts of the international and domestic context to development of science, technology and innovation in Vietnam for the period to 2030 - Hoang Minh; Nguyen Lan Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The international and domestic context have an important impact on determining the orientation of science, technology and innovation development in Vietnam for the period to 2030. The article uses the analysis tool PESTLE to identify major political, economic, social, technological, legal and environmental trends that affect Vietnam’s STI. With those trends, conducting a SWOT analysis to determine the impact of the context on Vietnam’s STI, including strengths to promote, limitations to overcome, opportunities to take advantage of and challenges to cope with. That is the basis for defining a number of viewpoints, goals, orientations, tasks and key solutions for the development of STI in Vietnam in the period to 2030. Code: 21121401